Biofuels : alternative feedstocks and conversion processes for the production of liquid and gaseous biofuels - Pandey, Ashok; Larroche, Christian; Gnansounou, Edgard; Khanal, Samir Kumar; Dussap, Claude-Gilles; Ricke, Steven (Biomass, biofuels, biochemicals., 2019)
Biomass, Biofuels, Biochemicals: Biofuels: Alternative Feedstocks and Conversion Processes for the Production of Liquid and Gaseous Biofuels, Second Edition, provides general information, basic data and knowledge on one of the most promising renewable energy sources-liquid and gaseous biofuels-and their production and application. The book delineates green technologies for abating environmental crisis and enabling the transformation into a sustainable future. It provides date-based scientific information on the most advanced and innovative technology on biofuels, as well as the process scale-up and commercialization of various liquid and gaseous biofuels, detailing the functional mechanisms involved, various operational configurations, influencing factors and integration strategies. All chapters have been updated, with new chapters covering topics of current interest, including sustainability and biohydrogen.